THE USE OF VERBAL AND NON-VERBAL COMMUNICATION BY FRONT OFFICE STAFF TO GUEST AT DOUBLE-SIX LUXURY HOTEL SEMINYAK - Sudantari, N.M. Nenty; Padmadewi, N.N.; Dewi, K. Sintya (Universitas Pendidikan Ganesha, 2019)
Verbal and non-verbal communication is important for hotel staff to communicate with the guest, thus ensuring their satisfaction. This study aimed at (1) finding out the forms of verbal and non-verbal communication used by front office staff, (2) describing the function of verbal and non-verbal communication used by front office staff, and (3) analyzing the difficulties faced by front office staff in using verbal and non-verbal communication. The subject of this study were the front office staff in Double-Six Luxury Hotel Seminyak. The main instrument used in gathering the required data was the researcher and the data were obtained through observation, audio recording, and interview. Four steps were done in analyzing the data, namely: data collection, data reduction, data display, and conclusion drawing. The result of the study showed that, the verbal language mostly used by front office staff in Double-Six Luxury Hotel Seminyak in handling guest related to the guest needs and SOP provided by the hotel. There were also non-verbal language used in the form of showing interest and happiness. The reason that verbal language is used according to the study is to make the communication run well and avoid misunderstanding among staff and guests. The language barrier led the staff to use non-verbal language but they were aware that using non-verbal language could lead to some politeness issue. Key words: communication, front office staff, guest, non-verbal, verbal